Optical Forward Scattering Property Employment for measuring the Atmospheric Visibility - مهند موسى عزاوي هشام عبد الملك اسماء عبد الرزاق سعيد (College of Education for Women, 2019)
Abstract An optoelectronic system for fog detection and visibility technique is presented .The idea of this research is based on the measurement of the atmospheric visibility by using an infrared beam emitter from LED diode. The optical scattering is used as a method to calculate the visibility. This method is applied at forward scattering within a foggy atmosphere, which is modern and has great importance for measuring visibility in seaports, airports, public roads and highways. In this paper we focus on the description of the system, principles of its operation and some results of field tests. Keywords: fog sensor, visibility sensor, backscattering, forward scattering.